The influence of social media marketing and brand image on buying interest in Gatsby Face Wash products at STIE Ekuitas Bandung - Maulani, Terra Saptina; Ramdan, Aryan Nur (Marketing Management Studies, 2025)
Gatsby face wash products at present have decreased compared to other products, Gatsby face wash products do marketing by utilizing social media marketing using Instagram but the strategy is not successful with many consumers who are not interested in posts from Gatsby face wash products because consumers think that Gatsby products are only found in hair oil, so that the strategy carried out by Gatsby face wash products also affects the brand image that is owned will decrease which causes consumer buying interest to decrease. This study uses descriptive and verification methods, the sample in this study was calculated by using the Taro Yamane formula. The results showed that partially and simultaneously social media marketing and brand image have a positive and significant influence on buying interest, so it can be said that social media marketing variables and brand image have a positive and significant effect together on buying interest.